Pemantauan Kadar Asam Urat Non Invasive Real Time Menggunakan Sensor Near Infrared - Umar, Usman; Alyah, Risnawaty (Lontara Journal of Health Science and Technology, 2020)
Gout or gout arthritis is a disease caused by the accumulation of monosodium uric crystals in the body. Uric acid is the result of the final metabolism of purines, which is a component of nucleic acids found in the body's cell nucleus. Increased uric acid can cause disturbances in the human body such as feelings of pain. The standard system used to measure uric acid levels in the blood, in general, is an invasive system that uses blood samples and is performed in clinics, health centers, and hospitals at a high cost. This research aims to develop a non-invasive system measuring gout using Near Infrared (NIR) sensor with 940 nm LED and Photodiode as a detector at a wavelength range of 600-1300 nm. The method of developing this tool begins with the stages, conducting a literature study resulting in tool design and tool making as well as tool validation by comparing invasive and non-invasive techniques. The results of this study produce a simple gout monitoring tool with an error value of 4% and low cost and easy to use. Analysis of the results of the tests using analysis of variance P-value> 0.05 and the t-test P (T <= t) 0.45> ? shows that the tool designed can be used to monitor gout.